KEADILAN LINGKUNGAN DAN PRINSIP PENCEMAR MEMBAYAR: ANALISIS PEMULIHAN KERUSAKAN LINGKUNGAN AKIBAT TAMBANG TIMAH DI BANGKA BELITUNG - Permatasari, bunga; Salfutra, Reko Dwi; robuwan, rahmat; Adha, Muhammad Yogie (Jurnal To Ciung : Jurnal Ilmu Hukum, 2025)
Legal and illegal tin mining activities have caused environmental damage in the Bangka Belitung Islands Province. This damage includes forest destruction, water and soil pollution, coastal abrasion, and loss of biodiversity. In environmental law, the polluter pays principle requires polluters to be responsible for the costs and actions to restore the damaged environment caused by their actions. In addition, environmental justice is also very important to uphold in the case of tin mining in the Bangka Belitung Islands Province. This study aims to analyze the application of environmental justice and the polluter pays principle in efforts to restore the environment caused by tin mining activities in the Bangka Belitung Islands Province. This study uses a normative juridical method with an emphasis on legislative and conceptual approaches. The focus of the analysis is directed at reviewing regulations and concepts related to the polluter pays principle and environmental justice theory, particularly within the framework of environmental damage restoration. The results of the study indicate that regulations in Indonesia have regulated the polluter pays principle, however, in practice, this principle faces obstacles in its implementation. In addition, the implementation of environmental justice is also carried out within the framework of environmental restoration. Therefore, the implementation of environmental justice needs to be carried out holistically. Political commitment, public oversight, and firm law enforcement are needed so that post-tin mining environmental recovery in Bangka Belitung not only improves the ecology, but also restores the rights of local communities who have been marginalized by the logic of natural resource exploitation.